Pengaruh Motivasi Kerja Terhadap Kinerja Karyawan Pada PT Media Intan Semesta Jakarta - Erri, Dirgahayu; Fajrin, Ashri Nur (www.bsi.ac.id, 2018)
Human resources is one of the factors that must be present and relatively more important than other factors, the Company should be able to increase employee motivation, employee motivation can have an impact on the achievement of coorporate goals. Employees are motivated to satisfy his need for work even harder the impact on the resulting performance becomes more optimal. PT Media Intan Semesta Jakarta is one of the companies engaged in the field of technology (IT). to win the competition takes motivation to work optimally so have employees with good performance in order to achieve company goals can be met. In this study, the authors use a quantitative methodology that uses statistical data SPSS V.22 author using 33 samples from 50 populations that are the result of a calculation formula slovin. It can be concluded that the influence of motivation on employee performance work PT Media Intan Semesta Jakarta can be seen from the results calculation correlation coefficient 0.891 meaning work motivation and performance of employees have a very strong relationship. 0,794 coefficient determination means the percentage work motivational influence on employee performance to 79,4% the remaining 20.6% is influenced by other factors not authors carefully. At a value of regression equation a (constants) 1,165 dan value of b coefficient 0.967. Keywords: Work Motivation, Employee Performance